TEACHER`S SKILLS IN DEVELOPING A CULTURE OF COMMUNICATION IN STUDENTS - Soliyeva Maftuna, Soliyeva Maftuna (Журнал иностранных языков и лингвистики, 2021)
This article is about the formation of a culture communication in the teaching profession. It analyzes the peculiarities and characteristics of communication during teaching process.